Respuesta :
Hello!
Let's solve !
⇒ (x - 3)² = 5
⇒ x² - 6x + 9 = 5
⇒ x² - 6x + 4 = 0
⇒ x = -(-6) ± √36 - 4(1)(4) / 2
⇒ x = 6 ± √20 / 2 = 6 ± 2√5 / 2
⇒ x = 3 ± √5
∴ The solutions are x = 3 + √5 and x = 3 - √5.
Answer:
p=(x−3)25
Step-by-step explanation:
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
(x-3)^2-(5*p)=0
STEP1:
1.1 Evaluate : (x-3)2 = x2-6x+9
Equation at the end of step1:
x2 - 6x - 5p + 9 = 0
STEP2:
Solving a Single Variable Equation:
2.1 Solve x2-6x-5p+9 = 0